MENCEGAH PENYEBARAN PAHAM RADIKALISME PADA SEKOLAH - Noermala Sary (Manthiq, 2017)
The problem discussed in this thesis is how the strategy of PAI clusters teacher in preventing the spread of radicalism in MAN 1 of Bengkulu City, and its supporting and inhibiting factors. The purpose of this study intends to describe the strategy of PAI teacher teachers in preventing the spread of radicalism in Madrasah AliyahNegeri1 Bengkulu  city, describing the  supporting factors  and  obstacles of PAI teachers in preventing the  spread of radicalism in Madrasah AliyahNegeri 1 Bengkulu  City. The method used  is descriptive qualitative  with the type of field research (field research). Data collection techniques: observation, interviews, and documentation. Data analysis  techniques: data  reduction, data  display  and  conclusion. The result  of the  research shows  that  the strategy of PAI teacher in preventing the spread of radicalism in MAN 1 is divided into two types: the strategy in the learning process in the classroom by using the active learning method and the Qur’an method of learning,  and the process Learning outside the classroom is: by holding various religious activities, forming a team  of worship in school, in cooperation with the police such as Sat. Bintal, and Sat. Binmas, in cooperation with the provincial kemenag, held  workshops and  religious socialization in schools.  Supporting  factors  in the implementation of prevention strategies of the  spread of radicalism in schools  is a sufficient  means of infrastructure both  from learning  resources, the  allocation of study time  and  teachers of the  PAI family. Inhibiting factors  are  misuse of informatics (IT) technology by students, the absence of special  programs in preventing the school’s  radical hazards, the lack of parental support for school policies, the lack of cooperation between schools with guardians, teachers with guardians, and the lack of Cooperation among  teachers.